Causes of Recurrent Urinary Tract Infection in Children on Prophylaxis - Sorkhi, Hadi; Shafi, Hamid; Hadipoor, Abass; Osia, Sohel; Batebi, Ornib (Journal of Pediatric Nephrology, 2013)
Introduction: Urinary tract infection (UTI) is a common pediatric problem. It has been estimated that 8% of girls and 2% of boys suffer from UTI during childhood. So, prevention of scar formation in high risk children is very important. This study was performed to evaluate the causes of recurrent urinary tract infection in children on prophylaxis. Materials & Methods: This study was performed on 141 cases in 126 children with recurrent UTI. A questionnaire was prepared and data including sex, age, grade of vesicoureteral reflux, and antibiotic used for prophylaxis were collected. Results: The mean age of the patients was 46.6±41.1 months; 24 % of the participants were male and 76% were female. The most common predisposing factor of recurrent UTI was vesicoureteral reflux. E.coli was the microorganism responsible for most of the cases (85.5%). In 85.5% of the children, Co-trimoxazole was used as prophylaxis. Drug resistance was the most common reason of recurrence. Conclusions: We conclude that girls are at higher risk of recurrent infection and regarding the high prevalence of Co-trimoxazole resistance, administration of this drug should be limited and with caution. Keywords: Urinary tract infections; Vesico-Ureteral Reflux; Drug resistance; Child